2019
DOI: 10.1016/j.biochi.2019.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Origins of peptidases

Abstract: a b s t r a c tThe distribution of all peptidase homologues across all phyla of organisms was analysed to determine within which kingdom each of the 271 families originated. No family was found to be ubiquitous and even peptidases thought to be essential for life, such as signal peptidase and methionyl aminopeptides are missing from some clades. There are 33 peptidase families common to archaea, bacteria and eukaryotes and are assumed to have originated in the last universal common ancestor (LUCA). These inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 67 publications
1
34
0
1
Order By: Relevance
“…Function reports of dipeptidases are mostly limited to virulence and growth in microorganisms, while there is little information regarding the effect of dipeptidases on stress tolerance in microorganisms. Family C69 dipeptidase is strictly distributed in fungi to ascomycetes (Rawlings and Bateman, 2019). Few studies were reported on PepDA in microorganisms and no functional analysis has been reported in fungi.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Function reports of dipeptidases are mostly limited to virulence and growth in microorganisms, while there is little information regarding the effect of dipeptidases on stress tolerance in microorganisms. Family C69 dipeptidase is strictly distributed in fungi to ascomycetes (Rawlings and Bateman, 2019). Few studies were reported on PepDA in microorganisms and no functional analysis has been reported in fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Peptidases (EC 3.4) are a class of enzymes to hydrolyze peptide chain to oligopeptides and single amino acids (Barrett, 1994). Peptidases can be classified into 261 families by catalytic mechanism as serine, cysteine, aspartyl, threonine, glutamic, or metallopeptidases (Rawlings and Bateman, 2019). For example, peptidases in which the nucleophile that attacks the scissile peptide bond is the sulfhydryl group of a cysteine residue are designated as cysteine-type peptidases (Rawlings et al, 2011;Barrett and Rawlingsm, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Протеазы играют ряд важнейших функций во всех живых организмах, и на долю кодирующих их генов приходится около 2 % от общего числа генов (Barrett et al, 2001;Rawlings et al,2004;Rawlings and Bateman, 2019). Пищеварительные протеазы, осуществляющие гидролиз пептидных связей в белках пищи, обеспечивают насекомых, как и другие организмы, аминокислотами -мономерами для построения собственных белков, а дефицит необходимых аминокислот ведет к негативным последствиям, вплоть до летального исхода.…”
Section: протеазыunclassified